Discus for dummies - Balke, N.
Author describes a simple model for the discus throw technique that anyone can learn and teach to others. He asks the following questions: 1. How to hold it? 2. How to release it? 3. How to perform the stand throw ? 4. How toperform the half throw? 5. The 3/4 and 7/8 throws 6. The full throw 7. Training to move correctly 8. Additional drills